Torsion of ovarian cyst in the third trimester of pregnancy: case report - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Putu Nining Gianni; Made Diah Vendita Sakuntari; Ni Wayan Dewi Purwanti; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Ni Komang Anik Pirgantari; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: The entire or partial rotation of the adnexa around its vascular axis or pedicle is known as ovarian torsion. Predisposing factors include short length, unrestricted motion, and a long pedicle. It’s tough to pinpoint the exact cause. Dermoid and serous cyst adenomas are the most common. The complete torsion blocks the venous and lymphatic systems, resulting in stasis, venous congestion, bleeding, and necrosis. The cyst becomes irritable and may explode. A soft cystic mass separate from the uterus can be seen on examination of the affected person, who usually complains of abrupt severe discomfort in the stomach and pelvis. At some time during pregnancy, the risk of ovarian torsion increases by a factor of five. The incidence rate is five per 10,000 pregnancies. Torsion of ovarian tumors was more common among women in their reproductive years. The majority of the instances were seen in pregnant women (22.7%) rather than non-pregnant women (6.1%). Case Description: In this case, we report a 27-year-old primigravida with 36 weeks and 5 days of pregnancy. She presented to the hospital with acute pain abdomen in the lower right (lumbar). She has a history of pregnancy control at a private clinic and there are no abnormalities in her pregnancy. She was hospitalized at 35 weeks 3 days of pregnancy due to the same complaint and has collaborated with the surgeon. No abnormalities were found on the abdominal ultrasound and urology at that time. The baby was born at 36 weeks 6 days of gestation by cesarean section, a twisted ovarian cyst was found on the right ovary, a dextra salpingectomy was performed for oophorectomy and an appendicectomy was also performed at the same time in collaboration with the surgeon. A healthy baby with a weight of 2300 grams and full of breastfeeding. Conclusion: This example demonstrates the problem of manufacturing desirable excellent radiological ultrasound imaging of the pelvic organs in late pregnancy. ultrasound exam in early pregnancy has to also be geared toward the cervix and adnexa which ends up in early analysis and management of ovarian hundreds, thereby fending off future emergency conditions and possible preterm transport.